Village Fund Corruption Reflects Weak Integrity of State Apparatus - Garini, Cherra Janua; Prasetyo, Yogi; Wibowo, Sugeng (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines transparency challenges and corrupt practices in village fund management in Madiun Regency. Issues discussed include the culture of patronage, regulatory deficiencies, and the low capacity of village officials, all contributing to corruption. Using a qualitative descriptive approach, data were collected through stakeholder interviews and document analysis. The study's findings indicate that misuse of village funds has resulted in significant losses to the state and undermined public trust. The cases in Sukosari and Gemarang demonstrate a pattern of systemic corruption through budget inflation and unrealistic procurement. The findings underscore the need for integrated reforms strengthening oversight mechanisms, enhancing village official capacity, and fostering community participation to achieve transparent and accountable village governance in village fund management, in order to create a transparent and accountable village government.